Metodologia de controle para equipamentos automáticos programáveis acionados por motores de passo - Roque, Alexandre dos Santos (2010)
Programmable devices require flexible control techniques. The ability the customize settings of the equipment reduces the cost and time of the design phases. On testing phases are commonly used commercial software or spent lot of time on developing hardware and software to specific control. This work proposes a methodology for flexible or configurable control, applied in equipments powered by stepper motors, which are widely used in academic projects and equipments with dedicated applications in industries. The methodology comprises characteristics considered fundamental to the parameterization of the equipment and the environment of operation. To facilitate future applications, the technique is presented using flowcharts and some behavioral diagrams of UML (Unified Modeling Language). To validate the proposed technique were developed a digital circuit and control software, implemented in the programming language C++, according to the characteristics presented in the methodology. The communication performed by USB protocol (Universal Serial Bus) follows the current trend of using this interface to control equipments through computers.